Dual incorporation of non-canonical amino acids enables production of post-translationally modified selenoproteins - Morosky, Pearl; Comyns, Cody; Nunes, Lance G. A.; Chung, Christina Z.; Hoffmann, Peter R.; Söll, Dieter; Vargas-Rodriguez, Oscar; Krahn, Natalie (Frontiers in Molecular Biosciences, 2023)
Post-translational modifications (PTMs) can occur on almost all amino acids in eukaryotes as a key mechanism for regulating protein function. The ability to study the role of these modifications in various biological processes requires techniques to modify proteins site-specifically. One strategy for this is genetic code expansion (GCE) in bacteria. The low frequency of PTMs in bacteria, makes it a preferred host to study whether the presence of a PTM influences a protein’s function. GCE employs orthogonal translation systems engineered to incorporate a modified amino acid at a designated protein position. Selenoproteins, proteins containing selenocysteine (Sec), are also known to be post-translationally modified. Selenoproteins have essential roles in oxidative stress, immune response, cell maintenance, and skeletal muscle regeneration. Their complicated biosynthesis mechanism has been a hurdle in our understanding of selenoprotein functions. As technologies for Sec insertion have recently improved, we wanted to create a genetic system that would allow the study of PTMs in selenoproteins. By recoding two stop codons (UAG and UGA), we were able to insert Nε-acetyl-L-lysine and selenocysteine, respectively, into multiple proteins. The specificity of these amino acids for their assigned position and the simplicity of reverting the modified amino acid via mutagenesis of the codon sequence demonstrates the capacity of this method to study selenoproteins and the role of their PTMs. Moreover, the evidence that Sec insertion technology can be combined with genetic code expansion tools further expands the chemical biology applications.